(untitled) (European Journal of Pure and Applied Mathematics, 2025)
We explicitly construct families of simple modules for all simple Lie algebras of rank 2 on which a certain commutative subalgebra acts diagonally with a simple spectrum. In type A, these modules are the well-known generic Gelfand-Tsetlin modules.